Exploring digital transformation challenges and opportunities in a short-term insurance company during hard lockdown - Nyoni, Thembinkosi (University of the Witwatersrand, Johannesburg, 2024)
Organisations have been digitalising, and by 2020, COVID-19 ignited acceleration towards digitalisation, with many organisations trying to enable two parties to business, employees, and customers to work remotely and access products, respectively. The objective of this study is to explore digitalisation challenges under COVID 19 lockdown, contribute to the existing body of knowledge of digitalisation and the success of future digitalisation initiatives. Due to benefits associated with digitalisation, prior to 2020, some organisations had opted to lead in this phenomenon, while others had brainstormed an idea with consideration of pros and cons. Since Covid 19 lockdown did not allow for formal steps to be taken to end up agreeing on digitalising, it was of interest to conduct a study around the development on challenges encountered and opportunities availed during the rushed approach. The research adopted a qualitative approach and gathered data through Microsoft teams virtual meetings on a one-on-one basis with seven participants out of ten invited. This approach allowed the researcher to take advantage of its strengths such as allowing participants to express their opinions freely. Participants were sampled using purposive sampling to ensure the right participants with the required level of authority were interviewed. Content analysis was used to unpack the collected data and required themes emerged. Findings identified challenges that were encountered by the leadership while digitalising during the Covid 19 lockdown. In as much as some maybe generic and expected in any project and environment, the most notable unique ones were restricted movement, collaboration difficulties, working with IT and testing system usability, external factors and logistics, and change management and client behaviour. These unique challenges align to the generalisation that if Covid 19 lockdown imposed a unique business environment, implementation of digitalisation initiatives during the lockdown faced unique challenges too. iii Antithetically, opportunities were identified during and after digitalising under Covid 19, realised, and seized because of digitalising under Covid-19 lockdown conditions. The most glaring opportunities included continuous improvement culture, effective decision making, work life balance, and lots of learnings. During the implementation, continuous improvement culture and effective decision making were immediately seized while work life balance and lots of learnings showed up at the end of the digitalisation initiatives. Considering theoretical frameworks applicable to this study, two were identified but were not of much value since they were put together during the Covid 19 lockdown, and these are the three block Digital Transformation Framework by Zaoui and Souissi (2020), the seven pillar Digital Transformation Framework by Javadi (2022). While the findings suggest that there were unique challenges and opportunities identified due to the lockdown situation, it implies that unique environments present unique challenges to be carefully considered when implanting a digitalisation initiative, while looking out for unique opportunities to look out for. Lastly, recommendations for further studies were put together seeing that digital transformation is still a new phenomenon
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Challenge, Digital; Digitalisation; Digitisation; UCTD; SDG-9: Industry, innovation and infrastructure